Study and simulation of resonant decays of the D MESON in the LHCB experiment - Abrantes, Fernanda Gonçalves (2017)
In many decays it is possible to observe the formation of an intermediate structure before the final state. The analysis of the Dalitz Plot offers a possibility to study resonant decays looking at the phase space. It’s possible to verify the presence of resonances with mass, width and spin well defined. Starting with a three body decay, , it was performed a simulation of a Dalitz Plot with the resonances K* and f comparing with a the same plot using real data from the LHCb.